STRATEGI KEPUTUSAN PENDANAAN UNTUK PENINGKATAN KINERJA KEUANGAN UMKM KULINER BERBASIS PRODUK LOKAL - Rita Tri Yusnita; Budhi Wahyu Fitriadi; Agus Peni Jaelani (LP2M Universitas Perjuangan Tasikmalaya, 2023)
Financial strategy is one of the company's functional strategies that aims to provide sufficient financial structure and funds to achieve company goals, and this is related to financing decisions. This study aims to determine the effect of capital structure and liquidity policies on profit growth and their impact on the financial performance of culinary MSMEs based on local raw materials in the city of Tasikmalaya. Data were taken from 33 samples of MSMEs using purposive sampling technique. Data were analyzed using multiple regression and linear regression analysis methods. The results of the descriptive analysis showed that the capital structure, liquidity, profit growth, and financial performance were in a fairly good category. The results showed that the capital structure and liquidity, either simultaneously or partially, had a positive and significant effect on the profit growth of culinary SMEs based on local raw materials in the city of Tasikmalaya. The results also showed that profit growth had a positive and significant impact on the financial performance of culinary MSMEs based on local raw materials in the city of Tasikmalaya. The results of this study indicated that MSMEs are quite successful in implementing financial strategies related to optimal capital structure policies and maintaining adequate levels of liquidity so that profit growth occurs, where profit growth can ultimately improve MSME financial performance. Keywords: capital structure, liquidity, profit growth, financial performance.